Bloqueo laparoscópico subcostal del plano transverso abdominal (TAP) como analgesia multimodal postquirúrgica en pacientes con patología biliar - Gálvez S, Patricio (2018)
Context: the postoperative pain is one of the main problems in surgical practices; it must be adequately treated to achieve a favorable evolution in the patient. Objective: To evaluate the laparoscopic subcostal block of the transverse plane of the abdomen with 0.5% of bupivacaine, versus the non-block in adult patients that had surgery of biliary pathology at San Francisco de Quito Hospital.Methodology: epidemiological study of cases and controls of patients that were admitted to the San Francisco de Quito Hospital. There are 210 patients equally divided in two groups, in the first group the subcostal block was applied, while in the other group was without intervention. The two groups were observed and assessed for 24 hours. The quantitative variables were reported as averages (± SD, Standard Deviation) and qualitative variables with their absolute and relative values (percentages) were also reported as well. The comparisons of quantitative variables were performed with a t-Student test, while the comparison of qualitative variables was performed with independent tests for proportions x2 and Fisher's exact test.Results: compared with the second group, the rate of analgesia for rescue was significantly lower in patients who received laparoscopic block with 0.5% bupivacaine (28.6% vs. 51.4%, respectively). The reduction in the use of analgesics was of 22.9% on average (95% CI: 36.7, 9%, p = 0.0012), equivalent to an OR: 0.38 (95% CI: 0.21, 0.67, p = 0.004). ORad = 0.38 (95% CI: 0.21, 0.67, p <0.01). The use of opioids was lower in the group with block compared to its control (46.7% vs 59.3%), the use of paracetamol was higher (30% vs 18.5%) and in the use of non-steroidal analgesics (NSAIDs), the result was similar (23.3% vs 22.2%).Conclusion: laparoscopic subcostal block is shown as an effective technique for pain control and treatment in patients that had surgery with biliary pathology, reducing the use of analgesia on average during the first 6 hours